1983
DOI: 10.1080/00223980.1983.9915403
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns in Patients with Cancer and Patients with Cardiac Disease

Abstract: Thirty cancer out-patients, 28 out-patients with cardiac disease, and 24 controls matched for age, sex, race, religion, and marital status were administered a 38-item questionnaire on sleep habits. Patients with cardiac disease perceived that they had more difficulty falling asleep, awakened earlier than planned, and felt sleepy during the day more often than the other two groups. Patients with cancer differed from controls only in feeling that they had more difficulty staying asleep. The findings demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 5 publications
3
31
0
Order By: Relevance
“…Early studies examined subjective sleep reports in cancer patients without objectively recording sleep and found that the patients with cancer had significantly more complaints of difficulty in sleeping than controls [8,28]. Whereas some studies supported the findings that women with breast cancer experience sleep problems [7,29,39], other studies have suggested that the sleep disturbance might be secondary to the pain and psychological distress experienced by these patients [24,25,42].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies examined subjective sleep reports in cancer patients without objectively recording sleep and found that the patients with cancer had significantly more complaints of difficulty in sleeping than controls [8,28]. Whereas some studies supported the findings that women with breast cancer experience sleep problems [7,29,39], other studies have suggested that the sleep disturbance might be secondary to the pain and psychological distress experienced by these patients [24,25,42].…”
Section: Introductionmentioning
confidence: 99%
“…Tiredness can also result from insomnia, which is a common problem of cancer patients (McCorkle & Quint, 1983;Cannici et al, 1983;Kaye et al, 1983;Silberfarb et al, 1985). Among other things, difficulty getting to sleep and difficulty staying asleep might result from pain.…”
mentioning
confidence: 99%
“…In the present study, we aimed to compare sleep disturbances in patients with GERD with the patients under treatment in oncology department, since little is also known about sleep quality in the people with cancer, whereas sleep disturbance is one of the most common symptoms in patients with malignancy [10][11][12][13][14][15][16]. Anxiety and depression, known as the most common factors influencing sleep quality, are also the most prevalent psychiatric disorders faced by patients with malignancy [17,18].…”
Section: Introductionmentioning
confidence: 99%